Torquing the Levers of International Power - Steven Ferrey (Washington University Global Studies Law Review, 2016)
The world is now at its climate’s “tipping point” at a precipice to redress global warming; after which our ability to halt a climate temperature rise below 2 degrees Centigrade (3.4 degrees Fahrenheit) is deemed unreachable. How to arrest the fast-accelerating accumulation of long-term carbon in the atmosphere is the legal and environmental challenge of the 21st century. It involves intelligent implementation of legal mechanisms, not technical fixes. Governments must quickly torque the levers of international power, but U.S. courts are finding some of these levers unconstitutional. This Article identifies, compares, contrasts, and torques the levers of international power. Sustainable development and continuation of world civilization in the manner we know it depend on effective and intelligent regulatory use of these comparative levers of power, and creation of legal space to do so. Part II of this Article explores why electric power forms the critical crucible in which climate, policy and law now mix. Part III examines the legal implications of feed-in tariffs, which European and other world nations employ to promote renewable electric power. Comparing U.S. to international experience, Part III then analyzes why these same techniques have been held unconstitutional in the U.S. when implemented by states. And even though legal in Europe, Part III examines the financial loss that has resulted from Germany’s, Italy’s, and Spain’s misaligned positioning of this lever of power. Part IV examines the alternative levers employed in the majority of U.S. states to promote renewable energy deployment: renewable portfolio standards and net metering. These are legal if carefully designed. However, the specific programs in several states have been found by federal Circuit Courts to violate the Constitution. A series of recent legal challenges has resulted in states having to legally remake their programs. Part V strategically manipulates these key international levers of power for the developed and developing countries of the world.
Keywords: Climate Change; Environmental Law; Constitutional Law; Feed-in-Tariffs; Renewed Portfolio Standards